The effects of Escherichia coli vaccination in gilts on piglets performance in a farm in Perak - Fong, Michelle Wai Cheng; Ooi, Peck Toung; Choo, Pow Yoon; Ong, Bee Lee; Tee, C. Y. (2012)
This study aimed to observe the effects of Escherichia coli (Neocolipor® vaccine) vaccination on neonatal diarrhoea score, growth parameters and neonatal mortality rate in newborn piglets. A field trial was conducted in 35 litters of piglets from gilts selected from a farm in Perak. Body weights of the piglets were measured at days 1, 7, 14 and 21 of age and the episodes of diarrhoea and piglet mortality were monitored daily. The Treatment group had significantly lower (p<0.05) neonatal mortality rate, day one neonatal diarrhoea percentage and diarrhoea in the overall period of 1- 21 days when compared to the Control group. However, there were no significant differences in the overall diarrhoea percentages and weekly growth parameters between groups (p>0.05). Environmental stress and routine treatment of diarrhoea with antimicrobials may have affected the significance of the diarrhoea score and growth parameters in this study. In conclusion, E. coli vaccination in gilts was shown to significantly reduce first week piglet mortality and diarrhoeal percentages on day one under farm conditions in this pilot study in Malaysia.